SAT0640 Diagnostic utility of detecting enthesitis by ultrasound in peripheral spondyloarthritis. (15th June 2017) - Fujikawa, K; Endo, Y; Mizokami, A; Mine, M; Kawakami, A
Abstract : Objectives: To evaluate the diagnostic utility of detecting enthesitis by ultrasound in patients with peripheral spondyloarthritis (SpA). Methods: A single-center cohort study was performed in patients with symptoms suggestive of peripheral SpA (inflammatory back pain, arthritis of the lower limbs, tenderness of the entheses and dactylitis). Patients with only axial symptoms in the absence of peripheral symptoms were excluded. Fourteen sites of enthesis (both sides of lateral epicondyle, quadriceps tendon insertion into the patella, patellar ligament insertion into the patella and tibial tuberosity, medial and lateral femoral condyles, and Achilles tendon) were assessed at baseline by ultrasound. Ultrasound assessment was made by Japan College of Rheumatology (JCR)-registered sonographers. Furthermore, articular synovitis and tenosynovitis of both wrist and finger joints as well as symptomatic sites were examined. Clinical, laboratory (CRP, HLA typing), radiological (X-ray and MRI of sacroiliac joint) findings and SpA classification criteria (Amor's, ESSG and ASAS) were also evaluated. The gold standard was the diagnosis made by the JCR-certified rheumatologists during a six-month follow-up period. Results: Between April 2014 and November 2016, one hundred-thirty six patients were consecutively enrolled. A definite diagnosis was obtained in 112 patients (72 SpA and 40 non-SpA). Diagnosis was not made in the remaining 24 patients. Seventy-two SpA patients (62 with undifferentiated SpA, 6 with psoriatic arthritis, 2 with AS, 1 with inflammatory bowel disease-associated arthritis and 1 with reactive arthritis) and 40 non-SpA patients were investigated in this study. In ultrasound findings, SpA patients showed power Doppler (PD) signals of the articular synovium (57%), tendon sheath synovium (71%) and enthesis (94%). A PD signal for at least one enthesis sites was the most useful finding for differentiation of SpA from non-SpA (sensitivity 94%; specificity 85%; accuracy 91%; positive likelihood ratio 6.3) regarding ultrasound findings. In logistic regression analysis, fulfillment of peripheral ASAS criteria, that of Amor's criteria, and presence of PD signals at least one enthesis sites were independent variables to the contribution of diagnosis of SpA (Figure 1 ). Conclusions: PD signals of entheses by ultrasound are useful for the diagnosis of SpA with peripheral joint symptoms. In addition to the consideration of axial SpA, the combination use of ultrasound with clinical classification criteria including ASAS and Amor's criteria is beneficial to diagnose peripheral SpA. Disclosure of Interest: None declared